Guidance Note on Jobs and Growth Issues in Surveillance and Program Work. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
This note provides operational guidance to staff on Jobs and Growth issues in surveillance and program work, building on the Board paper 'Jobs and Growth: Analytical and Operational Considerations for the Fund' (hereafter, 'Board paper'). Jobs and Growth issues can be defined broadly as issues relating to GDP growth, employment, and income distribution. The Board paper noted that work on these issues needs to be consistent with both the Fund's mandate and its areas of expertise. On a number of structural issues, especially related to labor market reforms and social protection schemes, the Fund would need to effectively collaborate with other institutions with greater relevant expertise.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet